2021
DOI: 10.3390/jof7110917
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Natural Function of Sophorolipids Produced by Starmerella bombicola

Abstract: The yeast Starmerella bombicola distinguishes itself from other yeasts by its potential of producing copious amounts of the secondary metabolites sophorolipids (SLs): these are glycolipid biosurfactants composed out of a(n) (acetylated) sophorose moiety and a lipid tail. Although SLs are the subject of numerous research papers and have been commercialized, e.g., in eco-friendly cleaning solutions, the natural function of SLs still remains elusive. This research article investigates several hypotheses for why S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Extracellular storage of usable energy in starvation emergency, and 2. Antimicrobial activity (De Clercq et al, 2021). Proteomic and genetic research on S. bombicola is recent, such as the study of its exoproteome (Ciesielska et al, 2014) and its transportome (Claus et al, 2022), demonstrating the potential of omics sciences for the functional design of molecular biosynthesis in industrial biotechnology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular storage of usable energy in starvation emergency, and 2. Antimicrobial activity (De Clercq et al, 2021). Proteomic and genetic research on S. bombicola is recent, such as the study of its exoproteome (Ciesielska et al, 2014) and its transportome (Claus et al, 2022), demonstrating the potential of omics sciences for the functional design of molecular biosynthesis in industrial biotechnology.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular storage of usable energy in starvation emergency, and 2. Antimicrobial activity(De Clercq et al, 2021).…”
mentioning
confidence: 99%
“…27 In addition, this work might provide a new perspective on the biological function of sophorolipids. Indeed, a recent study has shown that these compounds could represent an extracellular energy storage form in yeasts, 60 and the highly dense and efficient molecular packing of liquid-crystalline phases may be an important advantage in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Although based on TAG levels S. bombicola might not qualify as an oleaginous yeast, the production of sophorolipids and similar metabolic adaptations require a reconsideration of the oleaginicity requirements. Furthermore, it has been defended that the natural purpose of sophorolipids for the cell is to create extracellular storage of energy‐rich molecules that can be consumed while at the same time presenting antimicrobial properties (De Clercq et al, 2021). If this storage is indeed the case, we would encounter a case in which S. bombicola falls out of the oleaginous definition only because it is accumulating lipids extracellularly instead of intracellularly.…”
Section: Revisiting the Definition Of Oleaginous Yeastsmentioning
confidence: 99%